Chapter Giuristi ed economisti nella massoneria italiana fra le due guerre - CONTI, Fulvio (Studi e saggi, 2020)
The article focuses its attention on a list of jurists and economists, all university professors, who were active in Italy in the period between the two world wars and were affiliated with Freemasonry. The survey is based on a sample of 27 individuals belonging to the Grand Orient of Italy (16 jurists and 11 economists or statisticians) and using a prosopographic approach reconstructs their scientific and professional activity. The article highlights that many of them had important positions in universities or held political and institutional roles of national importance. The author carries out some reflections on the reasons that led such a large number of teachers to join the Freemasonry and on the influence that through them it could exercise on the political and cultural life of Italy.